Elephantine, Ägypten: Stadt und Tempel - Arnold, Felix; Seidlmayer, Stephan J.; Sigl, Johanna (e-Forschungsberichte des DAI, 2023)
The site of the ancient town on Elephantine island, close to present-day Assuan, offers the nearly unique chance to explore the structures and functions of an Ancient Egyptian provincial settlement from its village origins in late prehistory to its role as an important administrative and cultic center in pharaonic and graeco-roman times even into late antiquity and the early middle ages. Work in 2012 and 2013 was centered on two main project complexes. The reconstruction of the decoration, cultic installations, and uses of the temple of Khnum resulted in new insights into the building history and the symbolic layout of this largest sanctuary on the island. A fresh start in the excavation of settlement areas, harnessing the full potential of archaeometric methodology, aims at achieving a full picture the ancient living experience in the town of Elephantine.